2014
DOI: 10.1124/dmd.114.057232
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Milk Thistle (Silybum marianum) on Human Cytochrome P450 Activity

Abstract: Milk thistle (Silybum marianum) extracts are widely used as a complementary and alternative treatment of various hepatic conditions and a host of other diseases/disorders. The active constituents of milk thistle supplements are believed to be the flavonolignans contained within the extracts. In vitro studies have suggested that some milk thistle components may significantly inhibit specific cytochrome P450 (P450) enzymes. However, determining the potential for clinically significant drug interactions with milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…The results of experiments on blood and urine collected in Days 0, 10, and 27 indicated that silymarin did not have toxicity (Valentová et al, ). In another trial on healthy people, oral intake of capsules containing 175 mg of milk thistle extract or 140‐mg silymarin three times a day for 14 days had no major toxicity, and no adverse reactions were observed (Kawaguchi‐Suzuki et al, ).…”
Section: Safety and Adverse Reactions Of Oral Silymarin In Humansmentioning
confidence: 99%
“…The results of experiments on blood and urine collected in Days 0, 10, and 27 indicated that silymarin did not have toxicity (Valentová et al, ). In another trial on healthy people, oral intake of capsules containing 175 mg of milk thistle extract or 140‐mg silymarin three times a day for 14 days had no major toxicity, and no adverse reactions were observed (Kawaguchi‐Suzuki et al, ).…”
Section: Safety and Adverse Reactions Of Oral Silymarin In Humansmentioning
confidence: 99%
“…To our knowledge, no clinical evidence has confirmed the significant metabolic interaction involving CYP2C9. Additionally, our group determined that the MT supplement Legalon ® had no significant effect upon TOLB pharmacokinetics when administered to healthy volunteers (Kawaguchi-Suzuki et al, 2014). In accordance with these clinical observations, our ex vivo model showed no significant inhibition by MT on human CYP2C9 ( Figure 1 ), even when samples contained relatively high plasma concentrations of silybin A and B ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potentially significant inhibition of CYP2C9, 3A and major hepatic UDP-glucuronosyltransferases (UGTs) by silymarin components have been reported in several in vitro studies (Beckmann-Knopp et al, 2000; Brantley et al, 2010; Doehmer et al, 2011; Sridar et al, 2004). However, most clinical BDI investigations have failed to confirm any clinically relevant BDI (Gurley et al, 2004; Kawaguchi-Suzuki et al, 2014; Rajnarayana et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetic parameter endpoints AUC last , AUC ∞ , and C max for midazolam and 1′‐hydroxymidazolam were evaluated using the standard bioequivalence approach in which the absence of a clinically relevant interaction was concluded if the 90% confidence interval (CI) for the geometric mean ratio (GMR) was not contained within the no‐effect bounds of 80% to 125% . Based on an intrasubject variation of 17% for midazolam AUC, a sample size of 12 subjects would provide at least 80% power to demonstrate that the 90%CI of the geometric mean ratio would fall within the no‐effect range of 80% to 125%. SAS version 9.3 was used for analysis (SAS Institute Inc, Cary, North Carolina).…”
Section: Methodsmentioning
confidence: 99%